2021
DOI: 10.3389/fmicb.2021.683130
|View full text |Cite
|
Sign up to set email alerts
|

Complete Nucleotide Sequence, Genome Organization, and Comparative Genomic Analyses of Citrus Yellow-Vein Associated Virus (CYVaV)

Abstract: Citrus yellow-vein disease (CYVD) was first reported in California in 1957. We now report that CYVD is associated with a virus-like agent, provisionally named citrus yellow-vein associated virus (CYVaV). The CYVaV RNA genome has 2,692 nucleotides and codes for two discernable open reading frames (ORFs). ORF1 encodes a protein of 190 amino acid (aa) whereas ORF2 is presumably generated by a −1 ribosomal frameshifting event just upstream of the ORF1 termination signal. The frameshift product (717 aa) encodes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 46 publications
(66 reference statements)
0
29
0
Order By: Relevance
“…Citrus yellow-vein disease (CYVD) was first reported Dr. L. G. Weathers in California in 1957 (Weathers, 1957) resulting in typical yellow vein symptoms. Recently, Kwon et al (2021) demonstrated that CYVD is associated with a virus-like agent, tentatively named CYVaV and is transmitted via grafting to virtually all citrus varieties. The virus appears to be closely related to unclassified virus-like RNAs in the family Tombusviridae specifically OULV (Kwon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrus yellow-vein disease (CYVD) was first reported Dr. L. G. Weathers in California in 1957 (Weathers, 1957) resulting in typical yellow vein symptoms. Recently, Kwon et al (2021) demonstrated that CYVD is associated with a virus-like agent, tentatively named CYVaV and is transmitted via grafting to virtually all citrus varieties. The virus appears to be closely related to unclassified virus-like RNAs in the family Tombusviridae specifically OULV (Kwon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kwon et al (2021) demonstrated that CYVD is associated with a virus-like agent, tentatively named CYVaV and is transmitted via grafting to virtually all citrus varieties. The virus appears to be closely related to unclassified virus-like RNAs in the family Tombusviridae specifically OULV (Kwon et al, 2021). Indeed, phylogenetic analysis of the RdRp and ORF1-3genes placed the CYVaV and OULV from the current study were in a well-supported cluster.…”
Section: Discussionmentioning
confidence: 99%
“…A putative umbra-like viral sequence was described here. Phylogenetic analysis of the RdRp placed this new umbra-like sequence tentatively named wheat umbra-like virus (WULV) in a well-supported clade that includes previously umbra-like associated RNAs (ulaRNAs) identified in strawberry, papaya, citrus, babaco, maize, and sugarcane [48][49][50][51][52]. The sequence homology of the RdRp between WULV and other ulaRNAs ranged from 40-65% and 45-60% at the nucleotide and amino acid levels, respectively, suggesting WULV is a novel member of ulaRNAs.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a group of viruses phylogenetically related to umbraviruses was characterized by a wide range of plant host species [ 6 , 7 , 8 , 9 , 10 , 11 ]. Their genomes displayed several differences in their organization, such as the number of genes, and the encoded proteins did not show similarity to known viral movement proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the viruses in this group rely on helper viruses; for example, encapsidation of papaya meleira virus 2 (PMeV2) is dependent on the capsid protein of papaya meleira virus (PMeV), a virus related to mycoviruses from the Totiviridae family [ 7 ]. Several other molecular and biological properties of the Citrus yellow-vein-associated virus have been studied [ 9 ], which, unlike PMeV2, does not rely on any other virus for systemic infection.…”
Section: Introductionmentioning
confidence: 99%